Biorefinery : from biomass to chemicals and fuels : towards circular economy - Aresta, Michele, 1940-; Dibenedetto, Angela; Dumeignil, Franck (De Gruyter, 2022)
This updated edition presents topical knowledge and technologies for the thermal, chemo- and enzymatic-catalytic conversion of biomass into chemicals, materials and fuels. International experts from academia and industry cover the complete value chain from raw materials into final products. A new focus discusses feedstock, processes and products in potential concepts of future biorefining.